2019
DOI: 10.1590/s1678-3921.pab2019.v54.00064
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate estimate of heritability for quality traits in tomatoes by the multiple factor analysis

Abstract: The objective of this work was to evaluate a multiple factor analysis approach to estimate heritability for quality traits in tomatoes (Solanum lycopersicum), taking as a reference the values of heritability obtained through the classical method offspring-parent regression. A total of 18 F3 tomato families originated from the selfing of 18 individuals from a second-cycle hybrid were evaluated. In both generations, ten quantitative traits related to fruit quality were assessed. The multiple factor analysis show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The coefficient of genetic diversity observed in this study ranged from 9.89-26.08% and was classified as high. Mawasid et al (2019) reported that a high heritability value indicated that this character had the potential to advance selection. The high heritability value and the high coefficient of genetic diversity suggest that genetic factors cause differences in performance between genotypes.…”
Section: Estimation Of Variance Components and Heritabilitymentioning
confidence: 99%
“…The coefficient of genetic diversity observed in this study ranged from 9.89-26.08% and was classified as high. Mawasid et al (2019) reported that a high heritability value indicated that this character had the potential to advance selection. The high heritability value and the high coefficient of genetic diversity suggest that genetic factors cause differences in performance between genotypes.…”
Section: Estimation Of Variance Components and Heritabilitymentioning
confidence: 99%
“…Previous studies used this coefficient for the analysis of the genotype × environment interaction (Vitelleschi and Chavasa 2015;Zuliani et al 2012). The coefficient RV can be associated with the general heritability of the data set (Del Medico et al 2019). This estimation would make possible to carry out, objectively, a multi-character selection to continue with new cycles of self-fertilization and, thus, obtaining a joint response in the components of fruit quality.…”
Section: Resultsmentioning
confidence: 99%
“…To achieve the proposed methodological objective, the three-way data analysis technique called Multiple Factor Analysis (MFA) was used. This methodology allows a global analysis of data tables in which the same group of individuals is described through a set of variables, evaluated in different conditions, moments in time or places, such as the global evaluation of genotypes of tomato in two successive generations (Del Medico et al, 2019Medico et al, , 2020 or to globally analyze banana clones evaluated through quantitative and qualitative variables (Del Medico et al, 2021). This analysis allows balancing the influence of the different conditions in order to analyze them simultaneously.…”
Section: Discussionmentioning
confidence: 99%